Biomagnification and tissue distribution of perfluoroalkyl substances (PFASs) in market‐size rainbow trout (Oncorhynchus mykiss). (12th July 2013) - Goeritz, Ina; Falk, Sandy; Stahl, Thorsten; Schäfers, Christoph; Schlechtriem, Christian
Abstract: The present study investigated the biomagnification potential as well as the substance and tissue‐specific distribution of perfluoroalkyl substances (PFASs) in market‐size rainbow trout ( Oncorhynchus mykiss ). Rainbow trout with an average body weight of 314 ± 21 g were exposed to perfluorobutane sulfonate (PFBS), perfluorohexane sulfonate (PFHxS), perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid (PFNA) in the diet for 28 d. The accumulation phase was followed by a 28‐d depuration phase, in which the test animals were fed with nonspiked trout feed. On days 0, 7, 14, 28, 31, 35, 42, and 56 of the present study, fish were sampled from the test basin for PFAS analysis. Biomagnification factors (BMFs) for all test compounds were determined based on a kinetic approach. Distribution factors were calculated for each test compound to illustrate the disposition of PFASs in rainbow trout after 28 d of exposure. Dietary exposure of market‐size rainbow trout to PFASs did not result in biomagnification; BMF values were calculated as 0.42 for PFOS, >0.23 for PFNA, >0.18 for PFHxS, >0.04 for PFOA, and >0.02 for PFBS, which are below the biomagnification threshold of 1. Liver, blood, kidney, and skin were identified as the main target tissues for PFASs in market‐size rainbow trout. Evidence was shown that despite relative low PFAS contamination, the edible parts of the fish (the fillet and skin) can significantly contribute to the whole‐body burden. Environ Toxicol Chem 2013;32:2078–2088. © 2013 SETAC